A MODEL FOR PROFESSIONAL LEARNING COMMUNITY TO ENHANCE LEARNING CENTER DEVELOPMENT OF MUEANG NONG BUA LAM PHU DISTRICT OF THE NON-FORMAL AND INFORMAL EDUCATION CENTER - Sangsai, Winai (Journal of Buddhist Anthropology, 2022)
The objectives of this research article were to development the model for professional learning community to enhance learning center development of Muang Nong Bua Lam Phu District of the Non-formal and Informal Education Center by research and development method. The data were collected from 43 teachers and staffs, 7 special experts and 5 scholar experts by Purposive sampling. The research and development process 4 steps as follow; 1) to study basic information of the model via reviewing of documents and related literature, conducting of a focus meeting and interview. 2) To create the drafting the model and checking and the models’ suitability assessment by scholar experts. 3) To implement the model and doing achievement summary report. And 4) to evaluate the model by questionnaires. Research data were mean, standard deviation, analyzed with content analysis in order to synthesize to derive at conclusions. The finding showed as follow: 1) The development for learning center based on the royal concept of Khok Nong Na model, that focus on community areas management for sustainable agriculture, participatory management principle, doing activities and expand best practice to public. 2) The professional community learning model consists of 5 components; 2.1) Principle, 2.2) objectives, 2.3) process 2.4) evaluation and 2.5) key success factors, and the procedure include 6 steps as follow: step 1: shared values and vision, step 2: intentional collective learning, step 3: collaboration, step 4: expert advice, step 5: reflection dialogue, step 6: expand best practice to public. 3) The results of implementation the model showed the school had 6 learning centers consist of 3.1) Learning base for sufficiency economy philosophy and new theory agriculture 3.2) Khok Nong Na Model 3.3) 30 square wah and sustainable land 3.4) Fertilizer and herb repellent 3.5) Animal lovers 3.6) Processing produce. And 4) the result of model evaluation in overall was at the highest level.